JUAL BELI EMAS SECARA KREDIT MENURUT PERSPEKTIF HUKUM ISLAM (Studi Bank Syariah Mandiri Kantor Cabang Pembantu Bogor Sudirman) - Wida Khoiriyah; Tubagus Rifqy Thantawi; Ermi Suryani (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
Buying and selling gold on credit is a contract of transferring assets in the form of gold from one person to another which is done by credit. This study aims to analyze the practice of buying and selling gold on credit in Gold Installment Financing products at Bank Syariah Mandiri KCP Bogor Sudirman and to analyze how the law is buying and selling gold on credit according to the perspective of Islamic law. This research is included in the type of descriptive qualitative research, by reviewing various kinds of literature and criticizing the problems that exist in the field of sales and contract sales carried out on credit in the context of gold as currency. Then the sale and purchase of gold is only allowed to trade gold when the contract is cash and the value is the same, but if the status of gold is a commodity then buying and selling gold on credit is legally permissible.